2013
DOI: 10.1242/jcs.079475
|View full text |Cite
|
Sign up to set email alerts
|

Signaling inputs to invadopodia and podosomes

Abstract: SummaryRemodeling of extracellular matrix (ECM) is a fundamental cell property that allows cells to alter their microenvironment and move through tissues. Invadopodia and podosomes are subcellular actin-rich structures that are specialized for matrix degradation and are formed by cancer and normal cells, respectively. Although initial studies focused on defining the core machinery of these two structures, recent studies have identified inputs from both growth factor and adhesion signaling as crucial for invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 169 publications
2
178
0
Order By: Relevance
“…Because invadosomes are transient dynamic structures, some areas of gelatin degradation were observed that were no longer associated with invadosome markers at the time of fixation. Together, these results indicate that synovial cells of arthritis patients produce typical invadosome structures similar to those produced by cancer cells or synovial cells from collagen-induced arthritis rats (5,42,43).…”
Section: Resultsmentioning
confidence: 57%
“…Because invadosomes are transient dynamic structures, some areas of gelatin degradation were observed that were no longer associated with invadosome markers at the time of fixation. Together, these results indicate that synovial cells of arthritis patients produce typical invadosome structures similar to those produced by cancer cells or synovial cells from collagen-induced arthritis rats (5,42,43).…”
Section: Resultsmentioning
confidence: 57%
“…72 Actin polymerization in the core of invadopodia is regulated by small Rho-family GTPases, mostly, CDC42, 1,28 which can directly activate the N-WASP-WIP complex, which, in turn, drives actin polymerization by the Arp2/3 complex. [73][74][75][76] Arp 2/3 actin nucleation is promoted by the severing activity of cofillin. [77][78][79] Additional reports indicate that actin polymerization in invadopodia of certain cancer cells (e.g., MDA-231 breast cancer cell line) can also be induced by specific Diaphanous-related formins, whose cell type specificity, and mode of action and regulation, are still unclear.…”
Section: The Invasive Domainmentioning
confidence: 99%
“…During tumor invasion, GBM cells from the tumor migrate towards the neighbouring normal tissue by extending their edge actin-rich cancer-specific membrane protrusions forming invadopodia with the ability to infiltrate and degrade physical barriers, such as basement membranes, extracellular matrix (ECM), and cell junctions by metalloproteinases (MMPs) [30,35,36]; podosome/invadopodia are identified for their high expression levels of F-actin and/or cortactin [46]. The role of IQGAP1 as a scaffold protein in the delivering process of MMPs has been demonstrated in cell lines and animal models, as C. elegans, zebrafish, sea squirt, mice and rat [33,40,47,48]. Figure 7 is a simplified model of some of the proteins involved in the podosome/invadopodia generation mechanism and a model of the involvement of IQGAP1 in GBM progression based on the present study.…”
Section: Iqgap1 In Gbm Astrocytes and Gscsmentioning
confidence: 99%